Effects of psychological and resource factors on perceived business performance and financial well-being of government retirees in business - Norhashim, Mariati (2013)
The purpose of the study was to investigate the impact that being in business has on the financial well-being (FWB) of government retirees in business. This study adopted a research approach from the perspectives of psychology and resource theories. The psychological variables were motivation, attitude towards ageing and entrepreneurial self-efficacy while the resource factors were human, social and financial capital. A questionnaire based survey was conducted in between July 2010 to January 2011 on government retirees who were in business throughout Malaysia that employed a cross sectional design. Forty one respondents were successfully interviewed. Statistical procedures for the analyses included descriptive analysis, correlation analysis and path analysis. Profiling the government retirees in business revealed that the majority of the respondents operated business in the services, trade or retail industries which were set up and fully owned by themselves. Resource wise, the majority had very low financial capital, human capital and social capital. A worrying finding was that a quarter had neither friends nor family in their social network. Only twenty per cent had family working with them in in their business. Most of the business started were low cost barrier business with half investing RM10,000 or less. Most started their business from their own savings, about a third took out money from their retirement account and a fifth took loans. Those who received government grants or borrowed were worse off in their FWB compared to those who were self-financed. In spite that, all but one of the respondents reported positive FWB even though four of them have negative net worth. Factors which have a negative impact on FWB were number of illnesses and number of dependents. Factors which appeared to influence strongly positive FWB were positive perceived business performance, positive attitudes towards ageing as well as good saving habits. Thus, policies and programmes designed to improve PBP will have an indirect impact on FWB. The findings suggested that those who approach the government agencies for assistance need more than mere financial aid. Two of the factors that were found to improve perceived business performance (PBP) was entrepreneurial self-efficacy (ESE) especially in terms of marketing and social capital in terms of having a friend in their businessrelated social network. However, PBP was not found to have any significant role as a mediating factor on resource and psychological factors towards FWB. Yet, financial capital did have a strong positive but independent impact on both PBP and FWB. Training, mentoring as well as providing a social platform for post-retirement businesspersons would be beneficial in improving the FWB of this at-risk group. Policies and programmes need to go beyond merely putting a financial scheme in place specifically for retirees who wish to venture into business. An agency or other form of intermediary is needed in order to identify potential RIB and provide a ready channel for formulating aid programmes.